TRADISI KOMUNIKASI DI PESANTREN - Nurdin, Ali (Institut Agama Islam Negeri Madura, 2015)
This research describes the communication process among members of Islamic Boarding School such as kiai, ustadz, and santri. Islamic Boarding School is a kind of spesific subculture with a different set of values compared to dominant culture in the community. Those values form a homogeneous behavior and attitude among the members of the Islamic Boarding School. These results indicate that the tradition of communication in Islamic Boarding School are represented through the communication process between kiai, ustadz, and santri Â which happened in such tradition as â€˜sowanâ€™, communication model â€˜klasikalâ€™, communication model â€˜bandonganâ€™, communication model â€˜wetonanâ€™, commu-nication model â€˜soroganâ€™, communication model â€˜musyÃ¢warahâ€™, and com-munication using symbols like â€œbell ring soundâ€ and calls. Values acculturation and culture â€œsantriâ€ could emerge as a result of the â€˜intra-culturalâ€™ com-munication process in Islamic Boarding School. Because of that homogeneous subcultures, the communication process in the Islamic Boarding School empha-sizes on the process of â€˜intra-culturalâ€™ communication.Copyright (c) 2015 by KARSA. All right reservedDOI: 10.19105/karsa.v23i2.727Â